2020
DOI: 10.15252/emmm.201911466
|View full text |Cite
|
Sign up to set email alerts
|

A paracrine activin A–mDia2 axis promotes squamous carcinogenesis via fibroblast reprogramming

Abstract: Cancer‐associated fibroblasts (CAFs) are key regulators of tumorigenesis and promising targets for next‐generation therapies. We discovered that cancer cell‐derived activin A reprograms fibroblasts into pro‐tumorigenic CAFs. Mechanistically, this occurs via Smad2‐mediated transcriptional regulation of the formin mDia2, which directly promotes filopodia formation and cell migration. mDia2 also induces expression of CAF marker genes through prevention of p53 nuclear accumulation, resulting in the production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 75 publications
6
46
1
Order By: Relevance
“…They include murine Inhba itself ( Supplementary Fig. 2e, f), reflecting the previously described activin autoregulation 28 , while other activin genes and also activin receptor genes were not regulated ( Supplementary Fig. 2c, right).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…They include murine Inhba itself ( Supplementary Fig. 2e, f), reflecting the previously described activin autoregulation 28 , while other activin genes and also activin receptor genes were not regulated ( Supplementary Fig. 2c, right).…”
Section: Resultssupporting
confidence: 60%
“…Consistent with an effect of activin on the dermis/granulation tissue, depletion of regulatory T cells reduced the healingpromoting effect of activin 27 . However, activin also promotes proliferation and migration of cultured fibroblasts and expression of collagen type I by these cells 21,28,29 , suggesting that it may promote healing via this cell type. Therefore, we use mice overexpressing activin in keratinocytes 21 as a model system to determine the effect of a single cytokine on the wound healing process across scales and we determine the underlying mechanisms in skin fibroblasts in vitro.…”
mentioning
confidence: 99%
“…Moreover, CAF depletion can have opposite effects and favour tumour growth (Rhim et al , ), suggesting that reprograming of CAFs into a less activated state could offer higher therapeutic benefits. Cangkrama et al () recent findings are in line with these observations.…”
Section: A Vicious Circle Between Cancer Cells and Fibroblastssupporting
confidence: 77%
“…Many potential molecular players contributing to CAF activation have been described, notably TGF‐β itself, inflammatory modulators (interleukins), DNA damage or stimulation of tyrosine kinase receptors by growth factors (Sahai et al , ). In this issue of EMBO Molecular Medicine , Cangkrama et al () elegantly describe how activin A, a transforming growth factor β (TGF‐β) family member, induces tumour‐promoting fibroblast phenotypes. The pro‐tumourigenic features of CAFs have been well described and range from CAF secretion of soluble factors and ECM proteins (Duluc et al , ) to mechanical interactions with cancer cells contributing to tumour invasion (Gaggioli et al , ; Sanz‐Moreno et al , ).…”
Section: A Vicious Circle Between Cancer Cells and Fibroblastsmentioning
confidence: 99%
“…These results suggested that DEQA restores type I procollagen expression by stimulating TGF-β via the effects on UVA-irradiated HDFs (i.e., Smad 2/3 phosphorylation, Smad 4 activation and Smad 7 inhibition). The TGF-β pathway was shown to be involved in the cancer-associated fibroblast (CAF) activation [ 35 ], using HDFs, and high collagen I expression was linked with normal fibroblast reprogramming in CAFs [ 36 ]. Considering the effects of DEQA on TGF- β signaling and collagen production in HDFs, further studies might promote translational applications of DEQA or its derivatives with detailed analyses of action mechanism, structure–activity relationship and effective doses.…”
Section: Discussionmentioning
confidence: 99%